Examining recent research in the field of sharing economy in tourism : bibliometric and content analysis - Ferjanić Hodak, Danijela (Array, 2020)
Sharing economy has become a rather troublesome concept and business model in the process of tourism development during the recent years. Despite its undoubtful economic benefits for service providers and consumers, there are numerous negative impacts which can be related to the sharing economy, ultimately leading to unsustainable tourism development on destination level. In general, sharing economy can be attributed numerous benefits, but in terms of tourism, it recently became closely related to the issue of overtourism, thus becoming one of the initiators of negative attitude of the local community towards the future tourism development. Therefore, the concept of sharing economy has been in the focus of numerous researchers during the last several years, with increasing number of papers being published since 2016. This research is focused on analyzing the evolution and importance of sharing economy within the tourism study. The focus is given to the bibliographic analysis of journal articles within the “sharing economy in tourism” search. Additionally, based on qualitative content analysis the aim is to identify current state of the research in this field and to determine research gap with respect to the issue of overtourism and to identify future research potentials.